Higher Serum 25-Hydroxy Vitamin D Is Associated With Better Measures of Bone Microarchitecture and Strength. (7th June 2021) - Garrahan, Margaret; Gehman, Sarah; Rudolph, Sara; Tenforde, Adam; Ackerman, Kathryn E; Popp, Kristin L; Bouxsein, Mary L; Sahni, Shivani
Abstract: Objectives: To determine whether serum 25-hydroxy vitamin D (25-OH D) levels are associated with bone microarchitecture and strength in a multi-racial cohort of young adults. We also determined if race and calcium intake modified these associations. Methods: This cross-sectional study included 176 young adults who identified as Asian, Black, or White (50% women). High-resolution peripheral quantitative computed tomography (HR-pQCT, 2nd generation) scans of the distal radius and tibia were used to assess bone microarchitecture and strength by micro-finite element analysis. We measured 25-OH D levels (ng/mL, immunoassay), dietary intake (Block's Food Frequency Questionnaire), and physical activity (questionnaire). We used linear regression to estimate the association between 25-OH D and standardized bone measures, adjusting for race, sex, age, weight, height, calcium intake, and physical activity. The interactions of 25-OH D with race and calcium intake (mg/d) were tested and models were stratified for significant interactions ( P < 0.05). Results: Mean age and BMI were 23.7 ± 3.1 years and 24.1 ± 3.1 kg/m 2, respectively. 43.9% of the subjects were vitamin D deficient (<20 ng/ml) with greater prevalence in Asian (38.9%) and Black (43.1%) compared to White (18.1%) subjects ( P < 0.001 for group differences). At the distal radius, higher 25-OH D was related with higher cortical area (β ± SE = 0.018 ± 0.006, P  = 0.005), cortical porosity (β ± SE = 0.023 ± 0.008, P  = 0.006) and failure load (β ± SE = 0.023 ± 0.007, P  = 0.001). At the distal tibia, higher 25-OH D was related with higher trabecular density (β ± SE = 0.020 ± 0.008, P  = 0.015), trabecular thickness (β = 0.016 ± 0.008 P  = 0.044) and lower trabecular separation (β ± SE = −0.017 ± 0.008 P  = 0.046). There were no significant interactions for 25-OH D and calcium intake. Significant interactions were seen for 25-OH D and race, with stronger associations observed in White compared to Asian or Black subjects. Conclusions: This study suggests that higher 25-OH D is associated with better bone microarchitecture and strength at the distal radius and tibia in young adults. As poor bone microarchitecture is associated with increased fracture risk, these findings may have implications for fracture risk later in life. Funding Sources: U.S. Army Medical Research Acquisition Activity.